2011
DOI: 10.1371/journal.pone.0017818
|View full text |Cite
|
Sign up to set email alerts
|

The Human Metapneumovirus Matrix Protein Stimulates the Inflammatory Immune Response In Vitro

Abstract: Each year, during winter months, human Metapneumovirus (hMPV) is associated with epidemics of bronchiolitis resulting in the hospitalization of many infants. Bronchiolitis is an acute illness of the lower respiratory tract with a consequent inflammation of the bronchioles. The rapid onset of inflammation suggests the innate immune response may have a role to play in the pathogenesis of this hMPV infection. Since, the matrix protein is one of the most abundant proteins in the Paramyxoviridae family virion, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These differences are probably the result of distinct pattern recognition receptors engaged by infectious and inactivated virus in DCs, such as Toll-like receptors, retinoic acid-inducible gene-1-like family receptors and protein kinase R. For instance, some Toll-like receptors may engage virion molecules present both in infectious and inactivated viruses, such as the hMPV matrix protein. 40 On the other hand, molecules such as protein kinase R, Toll-like receptor 3, and retinoic acid-inducible gene-1-like family receptors are specialized at recognizing RNA species that mainly occur in replicating viruses. [41][42][43] However, despite the recognition of viable or inactivated virus (UV-treated), we observed that DCs secreted poor amounts of cytokines that support T-cell activation, such as IL-12 and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are probably the result of distinct pattern recognition receptors engaged by infectious and inactivated virus in DCs, such as Toll-like receptors, retinoic acid-inducible gene-1-like family receptors and protein kinase R. For instance, some Toll-like receptors may engage virion molecules present both in infectious and inactivated viruses, such as the hMPV matrix protein. 40 On the other hand, molecules such as protein kinase R, Toll-like receptor 3, and retinoic acid-inducible gene-1-like family receptors are specialized at recognizing RNA species that mainly occur in replicating viruses. [41][42][43] However, despite the recognition of viable or inactivated virus (UV-treated), we observed that DCs secreted poor amounts of cytokines that support T-cell activation, such as IL-12 and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…157 The M protein, which participates in virus assembly and packaging, 158 stimulates the inflammatory response in vitro by inducing the maturation of monocyte-derived DCs and the secretion of inflammatory cytokines by these cells, including IL-8, IL-6, IL-1b and TNF-a ( Table 2). 159 In addition, the M2-1 protein is critical for hMPV replication and pathogenesis through its Zinc binding activity, since a recombinant hMPV carrying mutations in the zinc binging motif was highly attenuated in cotton rats. 160 This is consistent with studies that demonstrate that hMPV lacking the M2-1 gene could not replicate in hamsters.…”
Section: Hmpv Molecular Characteristics and The Role Of Its Viral Promentioning
confidence: 99%
“…The significance of the spherical M protein staining pattern is unclear, but does suggest that in addition to the virus particle associated M protein, a second population of the M protein that does not show a similar staining to that observed using either anti-G or anti-F staining. This alternative M protein staining pattern may be related to the cell-free form of the M protein that has been described in HMPV-infected cells [ 22 ]. In addition, our previous studies employing recombinant expression to generate HMPV virus like particles (VLPs) [ 23 ] identified a population of the HMPV M protein that was secreted within membrane vesicles but which did not co-purify with the VLPs [ 23 ].…”
Section: Resultsmentioning
confidence: 99%